PERNIKAHAN WANITA HAMIL DI LUAR NIKAH TINJAUAN MENURUT EMPAT MADZHAB - Rionaldi (JURNAL CERDAS HUKUM, 2023)
In modern times the phenomenon of marriage of pregnant women outside of marriage is quite frequent. In general, the marriage takes place between a pregnant woman out of wedlock and a married person, sometimes also with someone else who has never touched her. Pregnancy without first marriage is certainly a gross sin and violates the principles and rules of Islamic law. In this context, scholars disagree on whether to marry a pregnant woman without going through marriage. The results of this study showed that Imama Abu Hanifah and Al-Syafi argued that pregnant women out of wedlock do not have iddah, so it is okay to marry. The permission to marry a woman who is pregnant out of wedlock is based on the hadith of Prophet Muhammad Saw, "A child is responsible for the owner of the bed. Meanwhile, the male who molested will only get disadvantages." (HR Bukhari and Muslim)." Furthermore, Imam Malik and Ahmad argued other people. According to him, A woman who is pregnant out of wedlock has an iddah. So it is not lawful for her to marry a woman who is pregnant out of wedlock until she gives birth. And the argument underlying the prohibition of marrying a pregnant woman refers to the Prophet's hadith which Ruwaifi ibn Tsabit said, "Whoever believes in Allah and the Last Day, never pour water on the land of another person's plant."